THE USE OF GREEN PRODUCTS IN HOUSEKEEPING DEPARTMENT AT KAMUELA VILLAS, LAGOI, BINTAN ISLAND - Illahi, Firman Wahyu (Jurnal Review Pendidikan dan Pengajaran, 2025)
This research aims to explore the use of environmentally friendly products (green products) in the housekeeping department at Kamuela Villas. The aim of this research is to find out how to implement the use of environmentally friendly products at Kamuela Villas in accordance with the Asean Green Hotel Standard guidelines. The research method used is a qualitative descriptive approach. Data was collected through in-depth interviews, direct observation and documentation. The respondent in this research is the Executive Housekeeper of Kamuela Villas. The results of the research show that Kamuela Villas already has a policy regarding the use of environmentally friendly products from the management of Archipelago International, but the implementation of Kamuela Villas management has not been comprehensive, this is due to considerations by management regarding the costs incurred to replace environmentally friendly housekeeping products as a whole.